2018
DOI: 10.1097/cxa.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Push and Pull: Migration Patterns and Links to Harm Reduction Services Among People Who Use Drugs

Abstract: Objectives: The role of migration among people who use drugs (PWUD) remains a complex topic that is often shaped by risk but also has the potential for protective health outcomes. This study examines migration trends and the effect of migration on the use of social support services for PWUD in Ottawa-Gatineau region. Methods: Respondent-driven sampling was used to recruit participants residing in Ottawa-Gatineau who were ≥18 years and used drugs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, there are also risks associated with this. Other studies have found that recent migrants in a period of "transition" were significantly less likely to access harm reduction and social support services, or be more likely to engage in risk behaviours [86,88,90,95]. The individuals in the current study noted having important connections locally to family, children, social networks, social services, among others.…”
Section: Physical Environmentmentioning
confidence: 43%
See 1 more Smart Citation
“…However, there are also risks associated with this. Other studies have found that recent migrants in a period of "transition" were significantly less likely to access harm reduction and social support services, or be more likely to engage in risk behaviours [86,88,90,95]. The individuals in the current study noted having important connections locally to family, children, social networks, social services, among others.…”
Section: Physical Environmentmentioning
confidence: 43%
“…As previously described, longer physical distances from services lead to reduced access and increased risk behaviours [46][47][48][49][50]. As one strategy to address distancerelated issues, other studies have highlighted a migratory element with relation to accessing services, with focus on people who use drugs [58,59,61,[86][87][88][89][90], as well as the interlinked field of mental health and homelessness services [91][92][93][94]. Perez Torruella [59] describes that such migration is encouraged by Puerto Rican authorities, on the basis of improved treatment access.…”
Section: Physical Environmentmentioning
confidence: 99%